Facile fabrication of rGO/Zr4+-Ni2+ gradient-doped BaM composites for broad microwave absorption bandwidth. Issue 3 (1st February 2021) - Liu, Chuyang; Zhang, Yanting; Gong, Haonan; Hu, Yunjia; Duan, Songhan; Peng, Kangsen; Zhu, Kongjun
Abstract: The combination of magnetic and dielectric materials is an effective and efficient approach to enhance microwave absorption performance. In this work, rGO/Zr 4+ -Ni 2+ gradient-doped BaM composites were fabricated for broad microwave absorption bandwidth. The results show that the permittivity increases while the permeability reduces gradually with the rising of rGO content. With the mass ratio of rGO increasing up to 15%, the relatively high attenuation constant and good impedance matching condition lead to an outstanding microwave absorption performance with a broad bandwidth of 8.16 GHz and a minimum reflection loss of −57.07 dB at a thin matching thickness of 2.0 mm. Compared with the pure gradient-doped BaM sample, the bandwidth has been widened by 37.37% and the minimum reflection loss has been improved by 220.43%. The performance is also superior to most of the existing state-of-art absorbers.